2012
DOI: 10.1089/rej.2011.1259
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Age-Related Decline of Kidney Function and Plasma Malondialdehyde

Abstract: Oxidative stress is a key factor linked renal function decline with age. However, there is still no large cohort study exploring the potential role of oxidative stress in mild insufficiency of kidney function (MIKF) and chronic kidney disease (CKD) after adjusting for confounding factors. This study tested the hypothesis that oxidative stress, indicated by plasma malondialdehyde (MDA), is associated with the prevalence of MIKF and CKD after controlling the effects of confounding factors. Plasma levels of MDA a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 44 publications
3
27
1
1
Order By: Relevance
“…MDA is generally believed to originate under stress conditions, and now it has been found to have high capability of reaction with multiple biomolecules such as proteins or DNA that leads to the formation of adducts [27]. It is further reported that excessive MDA production have also been found to be associated with different pathological states [28][29][30][31]. Hence, higher anti-inflammatory activity in SGE of H. dromedarii ticks might have helped the ticks to feed better by controlling inflammatory response mediated vasoconstriction during tick bite which is also in accordance with increased free radical scavenging activity and overall antioxidant status in these ticks.…”
Section: Discussionmentioning
confidence: 99%
“…MDA is generally believed to originate under stress conditions, and now it has been found to have high capability of reaction with multiple biomolecules such as proteins or DNA that leads to the formation of adducts [27]. It is further reported that excessive MDA production have also been found to be associated with different pathological states [28][29][30][31]. Hence, higher anti-inflammatory activity in SGE of H. dromedarii ticks might have helped the ticks to feed better by controlling inflammatory response mediated vasoconstriction during tick bite which is also in accordance with increased free radical scavenging activity and overall antioxidant status in these ticks.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress and inflammation promote the development and progression of chronic kidney disease [Nicholas et al, 2012]. Oxidative stress is a key factor linked to renal function decline with age [Li et al, 2012]. Kidney disease progressing to end stage is an increasing burden to patients and society in general.…”
Section: Cisplatin (Cis-diamminedichloroplatinum II Cddp)mentioning
confidence: 99%
“…Oxidative stress-related acute renal injury was reported to increase the reactive oxygen species and nitrogen species levels but to decrease the content of endogenous antioxidants [28] . As an indicator of oxidative stress, high levels of MDA in plasma exert an increasing burden on the renal system and accelerate the cycle of oxidative stress in the human body, leading to kidney function decline [29] . It is well-accepted that SOD plays an important role in the endogenous defense system against free radicals such as O 2− and H 2 O 2 [30] .…”
Section: Discussionmentioning
confidence: 99%